Refusal Strategies Used by EFL Learners of English Study Program in Riau, Indonesia - Ranisha Pristania Rusdi; Indah Tri Purwanti; Dahnilsyah Dahnilsyah (Institut Agama Islam Negeri Palopo, 2022)
This research shed light on the types of refusal strategies employed by the EFL learners of the English Study Program of Universitas Riau. This is using a descriptive qualitative study. The participants of this research involved 35 EFL students of the English Study Program selected by using the cluster random sampling method. The data was acquired using a DCT (Discourse Completion Task) as the instrument that contains some situations in which students were supposed to expressing their refusal. The result showed that the students used three kinds of strategies in giving refusals. Indirect refusal is the most strategy used by the students to interact in their daily life. One strategy which is not used by the students is direct refusal by using a performative statement.